1997
DOI: 10.1164/ajrccm.155.1.9001310
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in sleep-disordered breathing in African-Americans and Caucasians.

Abstract: In this case-control family study of sleep-disordered breathing (SDB), we describe the distributions of SDB and SDB risk factors in African-Americans and Caucasians. A total of 225 African-Americans and 622 Caucasians, ages 2 to 86 yr, recruited as members of families with an individual with known sleep apnea (85 index families) or as members of neighborhood control families (63 families) were studied with an overnight home sleep-study, questionnaires, and physical measurements. A subsample underwent cephalome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
354
2
12

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(382 citation statements)
references
References 15 publications
14
354
2
12
Order By: Relevance
“…Investigators have examined whether heritable factors can be implicated as determinants of sleep apnea susceptibility. Recent studies demonstrating familial aggregation and a racial predisposition to sleep apnea in individuals of African-American and Asian descent have suggested that heritable factors contribute to the development of sleep apnea (46)(47)(48) and to upper airway structural phenotypes (49). Further studies of the Cleveland Family Study cohort have demonstrated that sleep apnea (AHI) and obesity phenotypes are heritable (50).…”
Section: Sleep Apnea Risk Factors: Roles Of Obesity Sex Fat Distribmentioning
confidence: 99%
“…Investigators have examined whether heritable factors can be implicated as determinants of sleep apnea susceptibility. Recent studies demonstrating familial aggregation and a racial predisposition to sleep apnea in individuals of African-American and Asian descent have suggested that heritable factors contribute to the development of sleep apnea (46)(47)(48) and to upper airway structural phenotypes (49). Further studies of the Cleveland Family Study cohort have demonstrated that sleep apnea (AHI) and obesity phenotypes are heritable (50).…”
Section: Sleep Apnea Risk Factors: Roles Of Obesity Sex Fat Distribmentioning
confidence: 99%
“…Reference 32 In clinical settings, as much as 80% of hypertensives receive a diagnosis of SDB. Reference 3,4 Rates of SDB are much higher among members of minority groups (16.3%) compared to Caucasians (4.9%). Reference 5 The mean respiratory disturbance index for African Americans is significantly higher than that for Caucasians (72.1 vs 43.3).…”
Section: Study Findingmentioning
confidence: 99%
“…3 One population-based study of adult Americans, ages 40-60 years, found that SDB rates were much higher among members of minority groups, with estimates indicating that 16.3% of ethnic minorities have X20 events/h as compared to 4.9% of non-Hispanic Whites. 4 This finding is in tandem with another prevalence study comparing community-dwelling older African Americans and Caucasians, finding that African Americans were experiencing severe SDB with a relative risk twofold as great (relative risk ¼ 2.13) as that of their counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irk: Afrika-Amerikan ırksal kökenlilerde ve Asyalılarda görülme sıklığı daha fazla bulunmuştur 15,31,33,34 .…”
Section: Obstruktif Uyku Apne Sendromu Fizyopatolojisiunclassified